Isolasi kitosan dari cangkang udang pisang (Penaeus sp) sebagai spesies endemik di pantai barat Aceh - Dwi Apriliani; Lia Handayani; Nadia Putri; Reza Zuhrayani; Faisal Syahputra (AGROINTEK, 2023)
Pisang shrimp shells are one of the most fisheries waste can be utilized as chitosan because it contains lots of chitin. In addition, Pisang shrimp is also an endemic shrimp species in Aceh, so research data related to its use as chitosan is still very limited. Isolation chitin compound by using 2 stages. The stages are demineralization and deproteination. The demineralization with 1 N HCl solution, ratio (1:12) w/v for 120 hours, and then the second demineralization reaction with 1 N HCl (1:5) w/v for 20 hours. deproteinization reaction used 3 N NaOH solution (1:10) w/v, at 90 ºC for 1 hour with 50 rpm. Reaction transformation chitin into chitosan using NaOH 50 % (1:10) w/v, at 120ºC, for 10 hours with 1000 rpm. Pisang shrimp shells that used as raw material were milled to uniform size of the sifted flour using a sieve of 100 mesh sieve. Pisang shrimp shells flour has characterized, water content 0.75 %; ash content 32.48 %; fat 2.12 % and N-total 34,13 %. The quality of chitosan were ash content 0.72 %; N-total 2.73 %, the degree of deacetylation 76 % and the yield of chitosan obtained was 23.6 %. the yield was calculated based on the chitosan produced from the amount of pisang shrimp shell flour used